Posterior Cortical Cognitive Deficits Are Associated With Structural Brain Alterations in Mild Cognitive Impairment in Parkinson’s Disease - Devignes, Quentin; Viard, Romain; Betrouni, Nacim; Carey, Guillaume; Kuchcinski, Gregory; Defebvre, Luc; Leentjens, Albert F. G.; Lopes, Renaud; Dujardin, Kathy (Frontiers in Aging Neuroscience, 2021)
Context: Cognitive impairments are common in patients with Parkinson’s disease (PD) and heterogeneous in their presentation. The “dual syndrome hypothesis” suggests the existence of two distinct subtypes of mild cognitive impairment (MCI) in PD: a frontostriatal subtype with predominant attentional and/or executive deficits, and a posterior cortical subtype with predominant visuospatial, memory and/or language deficits. The latter subtype has been associated with a higher risk of developing dementia. Objective: To identify structural modifications in cortical and subcortical regions associated with each PD-MCI subtype. Methods: 114 non-demented PD patients underwent a comprehensive neuropsychological assessment as well as a 3T magnetic resonance imaging scan. Patients were categorized as having no cognitive impairment (n=41), frontostriatal (n=16), posterior cortical (n=25) or mixed (n=32) MCI subtype. Cortical regions were analyzed using a surface-based cortical thickness method. In addition, volumes, shapes and textures of the caudate nuclei, hippocampi and thalami were studied. Tractometric analyses were performed on associative and commissural white matter tracts. Results: There were no between-group differences in volumetric measurements and cortical thickness. Shape analyses revealed more abundant and more extensive deformations fields in the caudate nuclei, hippocampi and thalami in patients with posterior cortical deficits compared to patients with no cognitive impairment. Decreased fractional anisotropy and increased mean diffusivity were also observed in the superior longitudinal fascicle, the inferior fronto-occipital fascicle, the striato-parietal tract and anterior and posterior commissural tracts. Texture analyses showed a significant difference in the right hippocampus of patients with a mixed MCI subtype. Conclusion: PD-MCI patients with posterior cortical deficits have more abundant and more extensive structural alterations independently of age, disease duration and severity, which may explain why they have an increased risk of dementia.